Decreased Macular Retinal Thickness in Patients With Pterygium - Wang, Feng; Liu, Li Qi; Liang, Rong Bin; Zhang, Li Juan; Shu, Hui Ye; Liao, Xu Lin; Pan, Yi Cong; Wu, Jie Li; Su, Ting; Shao, Yi (Frontiers in Neurology, 2022)
Purpose To explore alterations in macular retinal thickness (RT) and analyze correlation between macular RT and pterygium area, length in pterygium patients. Methods Totally 13 patients with pterygium (left eye) and 13 healthy controls (left eye) were recruited. OCTA was applied to scan each eye to generate three-dimensional images. Based on the Early Treatment Diabetic Retinopathy Study (ETDRS) method, each image was divided into nine subregions for the ETDRS: central (C); inner superior (IS); outer superior (OS); inner nasal (IN); outer nasal (ON); inner inferior (II); outer inferior (OI); inner temporal (IT); and outer temporal (OT). The macular RT in each subregion was measured. Furthermore, the correlation between RT and the area, length of pterygium was analyzed. Results The visual acuity of pterygium patient was different from that of the control (P < 0.05). Besides, decreased intraretinal thickness of the IN and ON, increased intraretinal thickness of OT, decreased extraretinal thickness of OT, IN, ON, OS, and decreased retinal full layer thickness of medial superior, OS, IN, ON, and II subregions in pterygium group were observed. There was a negative correlation between RT of the IN and ON subregions and the length of pterygium (r = −0.5803 and r = −0.6013, P = 0.0376 and P = 0.0297). The RT of IN subregion was negatively correlated with pterygium area (r = −0.5844, P = 0.0359). According to the receiver operating characteristic analysis, in the ON subregion, the areas under the curve of the inner retinal thickness, outer retinal thickness and the whole retinal thickness were 1.0 (95% CI: 1.0), 0.882 (95% CI: 0.715 and 0.963), and 1.0 (95% CI: 1.0). The smallest area under the curve of retinal thickness in OT subregion was 0.018 (95% CI: 0–0.059). Conclusion RT of pterygium patients was significantly decreased, and the main alterations occurred in the temporal side suggesting there might exist retinal structural alterations in pterygium.